Risky human capital investment, income distribution, and macroeconomic dynamics - Volker Grossmann (Institute for the Study of Labor (IZA), 2003)
This paper analyzes the interaction between intergenerational wealth transmission, human capital investments under uninsurable labor income risk, and economic growth in a small open overlapping-generations economy with heterogeneous agents. It demonstrates how the role of the personal income distribution for an economy?s process of development through risky human capital accumulation depends on the shape of the saving function. Consistent with recent empirical evidence, the analysis suggests that the impact of higher inequality on the aggregate human capital stock, and thus, on growth may be positive. This result rests on two features of the model, which both are largely supported by empirical evidence. First, as shown under weak conditions, children?s human capital investments are positively affected by parents? income. Second, the marginal propensity to save is increasing in income.
Keywords: O11; O40; I20; 330; growth; income distribution; intergenerational transfers; risky education; saving function; Bildungsinvestition; Risiko; Einkommensverteilung; Privater Transfer; Sparen; Wirtschaftswachstum; Overlapping Generations; Theorie